Compatibility of Neoseiulus paspalivorus and Proctolaelaps bickleyi, candidate biocontrol agents of the coconut mite Aceria guerreronis: spatial niche use and intraguild predation - Lawson-Balagbo, L.M.; Gondim, M.G.C.; Moraes, G.J. de; Hanna, R.; Schausberger, P. (Springer, 2008)
The eriophyid mite Aceria guerreronis occurs in most coconut growing regions of the world and causes enormous damage to coconut fruits. The concealed environment of the fruit perianth under which the mite resides renders its control extremely difficult. Recent studies suggest that biological control could mitigate the problems caused by this pest. Neoseiulus paspalivorus and Proctolaelaps bickleyi are two of the most frequently found predatory mites associated with A. guerreronis on coconut fruits. Regarding biological control, the former has an advantage in invading the tight areas under the coconut fruit perianth while the latter is more voracious on the pest mites and has a higher reproductive capacity. Based on the idea of the combined userelease of both predators on coconut fruits, we studied their compatibility in spatial niche use and intraguild predation (IGP). Spatial niche use on coconut fruits was examined on artificial arenas mimicking the area under the coconut fruit perianth and the open fruit surface. Both N. paspalivorus and P. bickleyi preferentially resided and oviposited inside the tight artificial chamber. Oviposition rate of P. bickleyi and residence time of N. paspalivorus inside the chamber were reduced in the presence of a conspecific female. Residence of N. paspalivorus inside the chamber was also influenced by the presence of P. bickleyi. Both N. paspalivorus and P. bickleyi preyed upon each other with relatively moderate IGP rates of adult females on larvae but neither species yielded nutritional benefits from IGP in terms of adult survival and oviposition. We discuss the relevance of our findings for a hypothetic combined use of both predators in biological control of A. guerreronis.